A problemática do fundamento da ordem pública na decretação da prisão preventiva - Santos, Vanice Nascimento dos (2012)
Sheltering on the guarantee of freedom as a fundamental right and taking into consideration that these rights are not absolute, it is essential to understand the situations that allow the restriction of that right. Should be offered to the company advertising the circumstances autorizadoras restricting their fundamental right to freedom, and thus be aware of when and why this right is restricted. In support, it is seen as essential for society to understand what is the foundation of public order in the adjudication of custody. Explained. The preventive on the ground in public policy, even understood as a guarantor of the criminal proceedings, deserves to be better detailed. A limitation of personal freedom, even cautiously, must be justified and based on the principle of legality. As said Pacelli extending the boundaries of the incriminating criminal law from the public, may result in undue restriction of individual procedural guarantees. The justification of preventive as guarantor of public order should be considered in the light of proportionality and adequacy of prison every case. This bias, there is proven the importance of further study on the subject.